Carbazole: A potent scaffold for antitubercular drugs - Sellamuthu S.; Gutti G.; Kumar D.; Singh S.K. (My University, 2025)
The control of Tuberculosis (TB) is becoming more challenging due to drug resistance. Therefore, there is a dire need for newer drugs to tackle the nuances of resistant strains. Many molecular scaffolds are in the pipeline against TB. Among them, carbazole has a distinct advantage over other scaffolds because of its various sources i.e. medicinal plants, coal tar, and synthesis, besides the excellent antitubercular efficacy. This review provides an overview of carbazole alkaloids and their synthetic derivatives reported against Mycobacterium tuberculosis H37Rv (Mtb). The structure-activity relationship is also established to understand the molecular requirements for design and development of more potent antitubercular drugs. © 2018 Bentham Science Publishers.